Homologation of Isocyanates with Lithium Carbenoids: A Straightforward Access to α-Halomethyl- and α,α-Dihalomethylamides - Pace, Vittorio; Castoldi, Laura; Mamuye, Ashenafi Damtew; Holzer, Wolfgang (Synthesis, 2014)
Treatment of widely available isocyanates with monohalolithium and dihalolithium carbenoids provides a valuable protocol for the one-pot preparation of α-halo- and α,α-dihaloacetamide derivatives. While monohalolithium carbenoids can be prepared by a smooth lithium–halogen exchange, the preparation of the corresponding dihalo compounds proved to be highly dependent on the base used to realize the deprotonation, with lithium 2,2,6,6-tetramethylpiperidine emerging as optimal. The clear advantages of the procedure are: (a) broad scope of isocyanates that can be employed; (b) preservation of the optical purity when chiral materials are used; (c) divergent access to different haloamides by simply selecting the homologating agents. We also report an application of Charette’s imidoyl triflate activation of a secondary amide to the synthesis of an α-chloro ketone and 15N NMR data for selected compounds.
Keywords: amides; carbenoids; lithiation; halides; nucleophilic addition